Provisional authority : police, order, and security in India - Jauregui, Beatrice (The University of Chicago Press, 2016)
Policing as a global form is often fraught with excessive violence, corruption, and even criminalization. These sorts of problems are especially omnipresent in postcolonial nations such as India, where Beatrice Jauregui has spent several years studying the day-to-day lives of police officers in its most populous state, Uttar Pradesh. In this book, she offers an empirically rich and theoretically innovative look at the great puzzle of police authority in contemporary India and its relationship to social order, democratic governance, and security. Jauregui explores the paradoxical demands placed on Indian police, who are at once routinely charged with abuses of authority at the same time that they are asked to extend that authority into any number of both official and unofficial tasks. Her ethnography of their everyday life and work demonstrates that police authority is provisional in several senses: shifting across time and space, subject to the availability and movement of resources, and dependent upon shared moral codes and relentless instrumental demands. In the end, she shows that police authority in India is not simply a vulgar manifestation of raw power or the violence of law but, rather, a contingent and volatile social resource relied upon in different ways to help realize human needs and desires in a pluralistic, postcolonial democracy. Provocative and compelling, Provisional Authority provides a rare and disquieting look inside the world of police in India, and shines critical light on an institution fraught with moral, legal and political contradictions.